2020
DOI: 10.3390/rs12152427
|View full text |Cite
|
Sign up to set email alerts
|

Geo-Location Algorithm for Building Targets in Oblique Remote Sensing Images Based on Deep Learning and Height Estimation

Abstract: To improve the accuracy of the geographic positioning of a single aerial remote sensing image, the height information of a building in the image must be considered. Oblique remote sensing images are essentially two-dimensional images and produce a large positioning error if a traditional positioning algorithm is used to locate the building directly. To address this problem, this study uses a convolutional neural network to automatically detect the location of buildings in remote sensing images. Moreover, it op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
(26 reference statements)
0
18
0
Order By: Relevance
“…The deviation of the projection point from the CCD center is m pixels and n pixels in the X C and Y C direction. Sensors 2022, 22,1903 4 of 25…”
Section: Geo-location Model Using the Traditional Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deviation of the projection point from the CCD center is m pixels and n pixels in the X C and Y C direction. Sensors 2022, 22,1903 4 of 25…”
Section: Geo-location Model Using the Traditional Methodsmentioning
confidence: 99%
“…In order to solve the problem that DEM data does not include the height information of a building, a geo-location algorithm for building targets, based on the image method, was proposed in [22]. A convolutional neural network was used to automatically detect the location of buildings, and the imaging angle was used to estimate the height of a building.…”
Section: Introductionmentioning
confidence: 99%
“…This approximate conversion consi and y directions separately. Thus, a simple reverse process is possible from posit image, and it will be shown that the detection result is significantly improved in t periments although the coordinate conversion can be accompanied by various inev errors [28,29]. In the experiments, the altitude h is set to 400 m; W and H are 3840 and 2160 pixels; a x and a y are set to AFOV of the camera, 70 • and 40 • , respectively; θ T is set to 60 • ; thus y H/2 is calculated at 692.8 m by Equation (1), and d H/2 is 800 m accordingly.…”
Section: Image-position Conversionmentioning
confidence: 99%
“…This approximate conversion consi and y directions separately. Thus, a simple reverse process is possible from posit image, and it will be shown that the detection result is significantly improved in t periments although the coordinate conversion can be accompanied by various inev errors[28,29].…”
mentioning
confidence: 99%
“…In all the above references, the authors either didn't take into account the effect of the systematic error [4,19,24,25], or just introduced it as a fixed bias [6,8]. Eliminating systematic error is the basis for improving the accuracy of target geo-location since it directly affects the geo-location accuracy and the filtering algorithms [6,[13][14][15][16][17] cannot eliminate systematic error.…”
Section: Introductionmentioning
confidence: 99%